2021
DOI: 10.7759/cureus.17136
|View full text |Cite
|
Sign up to set email alerts
|

Tricuspid Valve Vegetation Secondary to Ovarian Cancer Leading to Acute Stroke via Pulmonary Arteriovenous Malformation

Abstract: We report a case of non-bacterial thrombotic endocarditis in a 52-year-old woman due to ovarian cancer that was complicated by acute ischemic stroke through pulmonary arteriovenous malformation. Echocardiography showed tricuspid valve vegetation and a positive bubble study that revealed pulmonary arteriovenous malformation in the absence of patent foramen ovale. The patient opted for palliative management and was discharged home with comfort care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
1
0
1
Order By: Relevance
“…Among 829 searched studies, 121 studies [ 19 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ...…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Among 829 searched studies, 121 studies [ 19 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ...…”
Section: Resultsunclassified
“…The flow chart of our included studies is shown in Supplementary Figure S1 . Around 25% (39) of included studies were from the USA, and only 1 study was reported from China [ 19 , 22 , 23 , 24 , 27 , 29 , 32 , 33 , 34 , 39 , 41 , 43 , 46 , 47 , 48 , 57 , 58 , 59 , 68 , 69 , 73 , 76 , 81 , 84 , 86 , 88 , 92 , 93 , 94 , 100 , 101 , 105 , 108 , 111 , 114 , 115 , 118 , 131 , 132 , 136 ]. A list of the included studies and the quality assessment are reported in Supplementary Table S2 .…”
Section: Resultsmentioning
confidence: 99%